2022
DOI: 10.3389/fnut.2022.823288
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Probiotics Reduces Chemotherapy-Induced Diarrhea and Oral Mucositis: A Systematic Review and Meta-Analysis

Abstract: BackgroundChemotherapy generally causes serious diarrhea and oral mucositis in cancer patients, and subsequently affects treatment. Oral administration of probiotics provides a therapeutic choice to address these limitations. This study aims to conduct a systematic review and meta-analysis on the efficacy of oral probiotic use in the management of the chemotherapy-induced adverse reactions, and to summarize the mechanisms underlying the action.MethodsWe searched PubMed, Embase, ClinicalTrials.gov, and Web of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 88 publications
2
28
1
1
Order By: Relevance
“…The results of the primary outcomes in our study demonstrated that probiotics significantly reduced the incidence of oral mucositis and severe oral mucositis following cancer treatment, which were consistent with previous studies [ 20 , 32 ]. In subgroup analysis, our findings revealed that probiotics significantly reduced the incidence of severe oral mucositis in patients receiving chemoradiotherapy, and the use of probiotics containing single strain lactobacilli was adequate to reduce the incidence of severe oral mucositis following cancer treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the primary outcomes in our study demonstrated that probiotics significantly reduced the incidence of oral mucositis and severe oral mucositis following cancer treatment, which were consistent with previous studies [ 20 , 32 ]. In subgroup analysis, our findings revealed that probiotics significantly reduced the incidence of severe oral mucositis in patients receiving chemoradiotherapy, and the use of probiotics containing single strain lactobacilli was adequate to reduce the incidence of severe oral mucositis following cancer treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Feng et al performed a meta-analysis to investigate the efficacy of probiotics in cancer therapy-induced oral mucositis [ 20 ]. According to their findings, probiotics exerted a significant protective effect against oral mucositis in cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the other studies (7,10,20,21,23,25), using multiple probiotic combinations, the probiotic groups showed a significant reduction in diarrhea. These findings are consistent with the study by Feng et al (28).…”
Section: Efficacysupporting
confidence: 94%
“…In the past five years, three high-quality meta-analyses ( 28 30 ) have studied the effectiveness of probiotics in avoiding radiation and chemotherapy-related adverse effects in cancer patients. Feng et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation